2015
DOI: 10.1016/j.techfore.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

How mismatching institutional logics hinder niche–regime interaction and how boundary spanners intervene

Abstract: The promotion of renewable energy production requires the cooperation of previously unrelated actors. In the Netherlands, a government subsidy pushes biomethane producers into a relationship with operators of the gas network. However, this cooperation proved to be very difficult. This research analyzes the problematic interaction between producers and network operators in the case of biomethane injection in the Dutch natural gas grid. We draw on the concept of 'institutional logics' to improve our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 54 publications
3
108
0
6
Order By: Relevance
“…When looking more closely at the underlying dynamics of facilitating multi-stakeholder innovation and building linkages between different actors at different levels, innovation system scholars have written about individuals who, for example, helped organizations to extend their organizational boundaries (i.e. boundary spanning; Klerkx et al 2010;Smink et al 2015) or leverage resources to push for institutional change (i.e. institutional entrepreneurs or innovation champions as described in Farla et al 2012;Klerkx et al 2009Klerkx et al , 2013Van Paassen et al 2014).…”
Section: Facilitating Connections Between Levels In Agricultural Innomentioning
confidence: 99%
“…When looking more closely at the underlying dynamics of facilitating multi-stakeholder innovation and building linkages between different actors at different levels, innovation system scholars have written about individuals who, for example, helped organizations to extend their organizational boundaries (i.e. boundary spanning; Klerkx et al 2010;Smink et al 2015) or leverage resources to push for institutional change (i.e. institutional entrepreneurs or innovation champions as described in Farla et al 2012;Klerkx et al 2009Klerkx et al , 2013Van Paassen et al 2014).…”
Section: Facilitating Connections Between Levels In Agricultural Innomentioning
confidence: 99%
“…Importantly, multiple logics structure socio-technical systems over time (Goodrick & Reay, 2011). While their principles often conflict with each other (Smink et al, 2015), some studies also note a complementary relationship between different institutional logics (Daudigeos et al, 2013). Whether conflicting or complimentary, this relationship forms a constellation of logics that defines dominant and innovative practices in socio-technical systems.…”
Section: The Institutional Logics Perspectivementioning
confidence: 99%
“…Indeed, these concepts can fruitfully be used to analyse the interaction between institutions and actors in transitions (e.g. Smink, Negro, Niesten, & Hekkert, 2015). While IL links institutional context and action, BS describes actors' strategic activities in diverse institutional working environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instance of such translation assumes that there are industry actors who will take a role as translators, thus promoting a broader industry-wide adoption of new technologies. Recent studies have shown that solid understanding of established practices, routines and standards within the existing regime is a prerequisite to be able to take this role (Bakker et al, 2015;Berggren et al, 2015;Elzen et al, 2012;Smink et al, 2015). Hence, translators build their legitimacy not only on participation in various local activities, but also on their existing position in the industry.…”
Section: Introductionmentioning
confidence: 99%